The Construction of a Socialized Service Platform and System for “Internet + Agriculture” in China - Run Tang; Qirui Liu; Ya Ou (Platforms)
The mismatch between supply and demand and inefficient supply in China’s agricultural product market is quite severe, making agricultural supply-side structural reform an important topic and task for rural economic work in China. The successful implementation of agricultural supply-side reform requires a comprehensive agricultural social service platform and system to support it. However, the current agricultural social service platform system in China faces issues such as a lack of coordination among service entities and poor information communication, making it difficult to meet the demands of supply-side reform. To address this issue, under the new circumstances of supply-side reform, this paper proposes the idea of reorganizing the agricultural social service platform and system through industrial chain collaboration theory, and applying “internet +” for technological reengineering of the agricultural social service platform system. Based on this, a new agricultural social service platform system architecture is constructed, which includes service entities, service platforms, service content, and operational models. The research findings provide guidance for agricultural product producers, distributors, sellers, and related service entities along the agricultural industry chain on how to use “internet +” for collaborative decision-making. This approach is beneficial for addressing the supply-demand imbalance and low resource allocation efficiency in China’s agricultural product market, thereby advancing the structural reform of China’s agricultural supply side.